Hypermedia patient data retrieval and presentation through WWW. - Tachinardi, U. (American Medical Informatics Association, 1995)
WWW can be a helpful tool for PACS and HIS data retrieval and presentation. The use of gateways to access both text and hypermedia databases (images and video) enables fetched data to be presented in virtually any computer system. WWW browsers provide a very friendly interface and require little training to operate. This paper presents a prototype that uses a SQL gateway for accessing relational patient databases. The dataset used here include text data from reports of diagnostic procedures as well as pointers to the corresponding images. Images can be displayed by the browsers' viewers.